Randomised controlled trial and cost consequences study comparing initial physiotherapy assessment and management with routine practice for selected patients in an accident and emergency department of an acute hospital. Issue 2 (20th January 2005) - Richardson, B; Shepstone, L; Poland, F; Mugford, M; Finlayson, B; Clemence, N
Abstract : Objective: The Department of Health is reviewing the effectiveness of accident and emergency (A&E) departments. This study aimed to compare health and economic effects of physiotherapy initial assessment and management with routine practice in an A&E department. Methods: Randomised controlled trial and cost and consequences study. Patients presenting at A&E were eligible if suspected at triage to have soft tissue injury without fracture. The efficacy end point was "days to return to usual activities". Secondary end points included patient satisfaction with their care and further health outcomes and cost data. Results: 766 of 844 (915) patients were randomised. The median days before return to usual activities (available for 73% of those randomised) was greater in the physiotherapist group (41 days compared with 28.5 days; hazard ratio 0.85 p = 0.071). The physiotherapy group expressed greater satisfaction with their A&E care (on a scale of 1 to 5, median was 4.2 compared with 4.0, p<0.001), were more likely to be given advice and reassurance, and more likely to be provided with aids and appliances. Costs were the same between the two arms. Conclusion: There is evidence that physiotherapy leads to a prolonged time before patients return to usual activities. This study shows no clear danger from physiotherapy intervention and long term outcomes may be different but given these findings, a best estimate is that introducing physiotherapist assessment will increase costs to the health service and society. Routine care should continue be provided unless there is some reason why it is not feasible to do so and an alternative must be found.